Medical authority in Indonesian clinical : An app-based telemedicine program - Chandrika Karisa Adhalia; Muhammad Fakih; Ria Wierma Putri (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background : Doctors who practice through application-based telemedicine do not have a clear legal regarding the services they provide. Telemedicine regulations that exist in Indonesia are still inadequate to cover all actions in telemedicine transactions, especially for legal protection for doctors who are legal subjects in this transaction. Given that until now, every telemedicine transaction must be under a Health Service Facility or an Online Doctor Consultation Service Provider. Thus, the doctor here as a provider of consulting services is actually not the main person who makes this transaction possibleMethod: Normative juridical approach, namely research conducted byhow to examine theories, concepts, legal principles and legislation related to this researchResults: Article 50 of law number 29 of 2004 concerning medical practice explains that a doctor has the right to obtain legal protection as long as his actions are in accordance with professional standards and standard operating procedures. In terms of application-based telemedicine, doctors do not have a practice permit, but during the COVID-19 pandemic, telemedicine was developed massively, the pandemic was considered an emergency, so the KKI regulation NUMBER 74 of 2020 concerning clinical authority and medical practice through telemedicine was issued during the COVID-19 period. The limit of clinical authority for application-based telemedicine practice is limited to consultation, not including medical action and administration of hard drugs.Conclusion: A doctor who has pocketed the STR is authorized to provide health services in accordance with his competence. The authority obtained by a doctor who has an STR is a form of recognition given by the government to the doctor concerned that he is worthy to provide health services in the form of medical practice. The limit of clinical authority for application-based telemedicine practice is limited to consultation, not including medical action and administration of hard drugs.